The Effect of the Micro -Teaching Method on the Physiological Level of Testosterone and Learning the Most Important Basic Skills in Fencing - Aqeel Yahya Hashim Abdulaziz (Journal of Global Pharma Technology, 2017)
The -teaching method is one of the modern methods in which all curricula have been taken ,It is one of the methods of teaching that has emerged in the field of modern teaching, which is a method of developing student XSTAP teaching skills, because it is a real teaching is not much different from full teaching training, it contains all the elements of teaching known .The fencing sport is one of the oldest known sports in the world, which has gradually expanded its attention to the increasing interest in its education and training. The researchers used the experimental approach on the students of the third stage in the Faculty of Physical Education and Sports Science University of Kufa (61) students, the tests were used to measure the physiological level of testosterone and to measure the level of performance of the most important skills in the duel. The researchers performed tribal tests and measurements on 27/11/2016, which included the withdrawal of a blood sample to measure the physiological level Testosterone, and then test the performance of basic skills in dueling and the preparation of units for teaching the method of -teaching and conduct post-tests. The researchers concluded that the use of the method of teaching micro-give the results of learning better, helping to achieve the objectives of educational exercises, the use of micro-teaching impact on the secretion of testosterone level, which reflects the strength of personality, and recommended the use of the method of teaching -achieving the objectives of educational exercises ,the use of micro-teaching in the development of personality traits, because the method of teaching -works to develop personal aspects ,and the use of the micro-teaching method with other samples of beginners in learning and with learners in the development of the skillful performance of the fencing .Keyword: Micro -teaching method, Testosterone, Learning , Basic skills and fencing .